Transversus abdominis plane (TAP) block with levobupivacaine versus levobupivacaine with dexmedetomidine for postoperative analgesia following cesarean delivery - Aman Varshney; Manjunath Prabhu; Bhavya Periyadka; Divyashri C Nanjundegowda; Amrut Rao (Wolters Kluwer Medknow Publications, 2019)
Background and Aims: Transverse abdominus plane (TAP) block provides good quality analgesia with minimal side effects. Addition of adjuvant like dexmedetomidine to the local anesthetics has been shown to prolong the action of the block in earlier studies. In this prospective randomised study TAP block with levobupivacane with or without dexmedetomidine was compared with control group for post-operative analgesia following cesarean delivery. Material and Methods: Ninety healthy women undergoing cesarean delivery under spinal anesthesia were randomized into three groups (GroupC, GroupL and Group LD). And following this Group L received ultrasound guided bilateral TAP block with 20 ml 0.25% levobupivacaine on each side, while Group LD received TAP block with same volume of levobupivacaine with 1μg/kg of dexmedetomidine. Group C, the control group did not receive TAP block. Postoperatively, time for first request for rescue analgesia and the number of women requesting analgesia in 6 h, 12 h and 24 h were noted. Pain score was measured with the Visual Analogue Scale (VAS) at rest and on movement for the first 24 h. Patient comfort and satisfaction with analgesia was evaluated at the end of 24 h. Results: Time for first rescue analgesia was significantly longer and patient satisfaction scores were significantly higher in patients who received TAP block (Groups LD and L) as compared to control (Group C). Pain scores were also lower in the TAP block groups compared to control group. Among the women who received TAP block, those with dexmedetomidine group (Group LD) asked for rescue analgesia significantly later compared to group L. Patient satisfaction score was highest in the Group LD compared to Group L which in turn was better than control group. There were no significant differences in the observed side effects. Conclusion: Bilateral TAP block with 0.25% levobupivacaine provides good quality analgesia for early postoperative period. Adding dexmedetomidine further improves pain control and gives higher patient satisfaction without any added side effects.